Lectotypification of Notonia grandiflora (Asteraceae: Senecioneae) - Wu, Xing; Guo, Xin-Qiang; Shao, Yun-Yun; Ren, Chen (Phytotaxa, 2020)
The controversy over the valid publication of Notonia grandiflora (Asteraceae: Senecioneae) is clarified, and the lectotype is designated for the name.